A Rapid Extraction and Analysis Method for the Simultaneous Determination of 26 Bioflavonoids in Portulaca Oleracea L. Issue 6 (29th May 2014) - Liang, Xiao; Li, Lingzhi; Tian, Jinlong; Wu, Yingying; Gao, Pinyi; Li, Danqi; Zhang, Qingyi; Song, Shaojiang
Abstract Introduction Portulaca oleracea L. (P. oleracea, purslane) is an edible plant that is widely distributed around the world, and flavonoids are its main bioactive constituents. Therefore, the detection of flavonoids is very important for a better understanding of its pharmacological actions and to monitor the product quality control of P. oleracea. Objective To develop a rapid method to extract and determine 26 bioflavonoids in P. oleracea, based on microwave extraction (MWE) and triple quadrupole‐linear ion trap mass spectrometry. Methods The optimal conditions of MWE for the extraction of flavonoids from P. oleracea involved the use of methanol as the extraction solvent, a microwave power of 300 W, an extraction time of 450 s, and a solvent‐to‐solid ratio of 30 mL/g. The samples were analysed using an ultra‐performance liquid chromatograph coupled with a triple quadrupole‐linear ion trap mass spectrometer (UPLC–MS/MS) system. Results The calibration curves of all 26 analytes showed good linearity (r ≥ 0.999) and the intra‐ and interday precisions and repeatability were all within required limits. The mean recoveries measured at three concentrations were higher than 94.2%, with RSDs lower than 2.94% for the targets. Conclusion The established MWE/UPLC–MS/MS method is a rapid and effective method for quality evaluation of P. oleracea from different production regions and different harvest periods. Copyright © 2014 John Wiley & Sons, Ltd.